2019
DOI: 10.1093/jbcr/irz159
|View full text |Cite
|
Sign up to set email alerts
|

Fireworks and Seafood Boils: The Epidemiology of Burns in Louisiana

Abstract: Epidemiological trends provide a means for targeting efforts in burn prevention. There have been but few regional-specific studies concerning burns in the southern United States. This study describes burn injury trends experienced by a single burn center in Louisiana. We also investigate the temporal relationships of several activities informally known for having a high risk for burn injury among local providers. Data were retrospectively extracted from the records of all patients treated for burn injuries at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, as expected, more kitchen-related burn injuries were sustained during the pandemic at home than at work. This is in keeping with prior studies as the kitchen is a common location for burn injuries at home [20] .…”
Section: Discussionsupporting
confidence: 87%
“…However, as expected, more kitchen-related burn injuries were sustained during the pandemic at home than at work. This is in keeping with prior studies as the kitchen is a common location for burn injuries at home [20] .…”
Section: Discussionsupporting
confidence: 87%
“…15 A study on the epidemiology of burns in Louisiana demonstrated that the annual burn incidence rate was highest among Black individuals, though white patients had the greatest incidence of severe burns with total body surface area (TBSA) >20%. 16 Black patients in Louisiana had higher burn rates in situations involving bathing, cosmetics, and seafood preparation, whereas whites had higher rates in automotive, bonfire, and smoking situations. 16 With regards to ED visits and admissions, one study showed burn rates for Black patients visiting the Emergency Department was 62% higher than for whites.…”
Section: Burn Epidemiology and Risk Factorsmentioning
confidence: 95%
“…16 Black patients in Louisiana had higher burn rates in situations involving bathing, cosmetics, and seafood preparation, whereas whites had higher rates in automotive, bonfire, and smoking situations. 16 With regards to ED visits and admissions, one study showed burn rates for Black patients visiting the Emergency Department was 62% higher than for whites. 17 Admission rates in that same study were lower for Black adult patients, though a different study on pediatric burn patients specifically found that Black children versus white children were over seven times more likely to be admitted for burn treatment.…”
Section: Burn Epidemiology and Risk Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the assessment of child and adolescent injury prevention and safety promotion in Poland made by Malinowska-Cieślik et al revealed that child home safety related to prevention of falls, burns and scalds, choking, and strangulation has not received adequate attention [5]. Information about the epidemiology of burns in children can provide a means for targeting efforts in burn prevention [6].…”
Section: Introductionmentioning
confidence: 99%